Inactivation of hepatocyte nuclear factor-4α mediates alcohol-induced downregulation of intestinal tight junction proteins - Zhong, Wei (American Physiological Society, 2010)
Chronic alcohol exposure has been shown to increase the gut permeability in the distal intestine, in part, through induction of zinc deficiency. The present study evaluated the molecular mechanisms whereby zinc deficiency mediates alcohol-induced intestinal barrier dysfunction. Examination of zinc finger transcription factors in the gastrointestinal tract of mice revealed a prominent distribution of hepatocyte nuclear factor-4α (HNF-4α). HNF-4α exclusively localizes in the epithelial nuclei and exhibited an increased abundance in mRNA and protein levels in the distal intestine. Chronic alcohol exposure to mice repressed the HNF-4α gene expression in the ileum and reduced the protein level and DNA binding activity of HNF-4α in all of the intestinal segments with the most remarkable changes in the ileum. Chronic alcohol exposure also decreased the mRNA levels of tight junction proteins, particularly in the ileum. Caco-2 cell culture studies were conducted to determine the role of HNF-4α in regulation of the epithelial tight junction and barrier function. Knockdown of HNF-4α in Caco-2 cells decreased the mRNA and protein levels of tight junction proteins in association with disruption of the epithelial barrier. Alcohol treatment inactivated HNF-4α, which was prevented by N-acetyl-cysteine or zinc. The link between zinc and HNF-4α function was confirmed by zinc deprivation, which inhibited HNF-4α DNA binding activity. These results indicate that inactivation of HNF-4α due to oxidative stress and zinc deficiency is likely a novel mechanism contributing to the deleterious effects of alcohol on the tight junctions and the intestinal barrier function.